Hysterectomy in India: Spatial and multilevel analysis. (June 2021) - Singh, Angad; Govil, Dipti
Objective: Using the unit-level data of women aged 15–49 years from National Family Health Survey-IV (2015–2016), the article maps the prevalence of hysterectomy across districts in India and examines its determinants. Methods: Descriptive statistics, multivariate techniques, Moran's Index and Local indicators of Spatial Association were used to understand the objectives. The data were analysed in STATA 14.2, Geo-Da and Arc-GIS. Results: In India, the prevalence of hysterectomy operation was 3.2%, the highest in Andhra Pradesh (8.9%) and the lowest in Assam (0.9%). Rural India had higher a prevalence than urban India. The majority of women underwent the operation in private hospitals. Hysterectomy prevalence ranged between 3% and 5% in 126 districts, 5% and 7% in 47 districts and more than 7% in 26 districts. Moran's Index (0.58) indicated the positive autocorrelation for the prevalence of hysterectomy among districts; a total of 202 districts had significant neighbourhood association. Variation in the prevalence of hysterectomy was attributed to the factors at the primary sampling unit, district and state level. Age, parity, wealth and insurance were positively associated with the prevalence of hysterectomy, whereas education and sterilization was negatively associated. Conclusion: Hysterectomy operation in India presented the geographical, socio-economic, demographic and medical phenomenon. The high prevalence of hysterectomy in many parts of the country suggested conducting in-depth studies, considering the life cycle approach and providing counselling and education to women about their reproductive rights and informed choice. Surveillance and medical audits and promoting the judicial use of health insurance can be of great help.